MANFAAT KOMBINASI JUS SELEDRI DAN TIMUN DALAM PENURUNAN TEKANAN DARAH TINGGI: MANFAAT KOMBINASI JUS SELEDRI DAN TIMUN DALAM PENURUNAN TEKANAN DARAH TINGGI - Husna Sari; Putri Ayu Yessy Ariescha; Marlen Sadrina Sitepu; Eka Sriwahyuni; Nanda Pratama; Nurcahaya Nainggolan; Uswatun Hasanah (Jurnal Pengabdian Masyarakat Putri Hijau, 2026)
Hypertension is one of the non-communicable diseases that remains a major public health problem with an increasing prevalence, especially among the elderly population. This condition is influenced by unhealthy lifestyles, lack of physical activity, and limited public knowledge regarding the prevention and management of hypertension. This community service activity aimed to improve community knowledge and awareness regarding blood pressure control through the utilization of complementary therapy in the form of a combination of celery and cucumber juice. The activity was conducted in Dusun IV, Patumbak I Village, Patumbak District, Deli Serdang Regency, May 15, 2026. The methods used included preliminary surveys, observations, interviews, health education, health screenings, hypertension exercise programs, and community empowerment activities. The target participants were residents of Dusun IV using a participatory approach. The results showed that hypertension was identified as a priority health problem in the community. After the implementation of health education and counseling, the community demonstrated high enthusiasm and improved understanding regarding hypertension risk factors, the benefits of a healthy lifestyle, and the use of celery and cucumber juice as a non-pharmacological therapy to help reduce blood pressure. This activity is expected to increase community awareness in preventing and controlling hypertension independently through the adoption of healthy lifestyles and the use of natural ingredients that are easily accessible in the surrounding environment.